Case study on language anxiety of Korean student-teachers in the Philippines - Ugalingan, Gina B. (Animo Repository, 2018)
Various studies on the different experiences of student-teachers who are non-native speakers of English emerged to strengthen teaching curriculum and empower these studentteachers to be equipped as they take the role of classroom teachers. Based on these studies, one of the issues experienced by non-native student-teachers is language anxiety. This case study aimed to identify if language anxiety is present and its possible sources among the eight (8) Korean student-teachers at the De La Salle University-Manila, Philippines during their practicum teaching. The participants of the case study were under the program of Bachelor of Secondary Education major in English. The study utilized different instruments, namely; Teacher Foreign Language Anxiety Scale (Horwitz, 2013), individual interview, and weekly reflections. Results showed that the participants experienced varying levels of language anxiety. Also, the common sources of their language anxiety were (1) perceived low language proficiency, (2) fear of committing mistakes, (3) lack of preparation, (4) classroom management, (5) fear of being observed and evaluated, (6) individual personality, and (7) cultural differences.